Investigation of the acaricidal activity of the acetone and ethanol extracts of 12 South African plants against the adult ticks of Rhipicephalus turanicus - Gerda Fouche; Bellonah M. Sakong; Olubukola T. Adenubi; Jean Paul Dzoyem; Vinny Naidoo; Tlabo Leboho; Kevin W. Wellington; Jacobus N. Eloff (Onderstepoort Journal of Veterinary Research, 2017)
The acaricidal activity of acetone and ethanol extracts of 12 plant species was evaluated using the contact method on Rhipicephalus turanicus (Acari: Ixodidae) ticks at an initial concentration of 20% (200 mg/mL). Eight of the 12 plants had mortality greater than 50% and the acetone extracts had better acaricidal activity than the ethanol extracts. The acetone extract of Calpurnia aurea (leaves and flowers) had the highest corrected mortality (CM) of 92.2% followed by Schkuhria pinnata (whole plant) with a CM of 88.9%, Ficus sycomorus (bark and stems) 86.7% and Senna italica subsp. arachoides (roots, leaves and fruits) 83.3%. Selected extracts were tested at five different concentrations using the adult immersion test. From dose–response assays, EC50 values of 61.82 mg/mL, 115.21 mg/mL and 161.02 mg/mL were obtained for the acetone extracts of S. pinnata (whole plant), S. italica subsp. arachoides (roots, leaves and fruits) and C. aurea (leaves and flowers) respectively. The ethanol extract of Monsonia angustifolia (whole plant) had the highest CM of 97.8% followed by S. pinnata (whole plant) with a CM of 86.7%, C. aurea (leaves and flowers) 81.1% and Cleome gynandra (leaves) 77.8%. There is potential for the development of environmentally benign botanicals as natural acaricides against R. turanicus.